Analisis Analisis Pembelajaran "Tari Hayu Batur" untuk Meningkatkan Kecerdasan Kinestetik Anak Usia Dini: Peningkatan kecerdasan kinestetik Melalui Pembelajaran "Tari Hayu Batur" - Rosa Nur Anisa; Sima Mulyadi; Rosarina Giyartini (Tunas Siliwangi, 2024)
Kinesthetic intelligence is intelligence where a person is skilled at using their body parts. Kinesthetic intelligence problems tend to have difficulty maintaining balance. This research aims at the importance of developing kinesthetic intelligence from an early age. The research uses a qualitative approach with descriptive methods. The methods used to collect data in this research include observation and interviews. In qualitative data analysis, there are three main stages, namely data reduction, data presentation, and drawing conclusions. The results of observations and interviews in Class B3 of Artanita Al- Khoeriyah Kindergarten, Hayu Batur dance learning provides changes, namely children with various difficulties are able to move all or part of their body, especially in coordinating movements between the head, legs and hands in an agile and flexible manner. Thus, learning the Hayu Batur dance has the potential to be a means of optimally increasing the development of kinesthetic intelligence in children.